Integrated Marketing Communication Practices In Malaysia Glcs And It Relationships With Local Cultures - Mohamad Yasin, Nazri; Md Yusoff, Mohamad (2015)
The continuous changes occurring in the field of marketing communications led to an increasing relevance of researches on integrated marketing communication (IMC). Due to the fast pace of technological innovations, IMC is going to be a very dynamic discipline. In this study, the four stages of IMC framework and cultural dimension theory are highlighted as a potential lens through which researcher analyzes the current practices and implementations of IMC in GLCs. The study was conducted on nine selected GLCs in Malaysia located in the Klang Valley. GLCs senior management, executives, and stakeholders were the respondents for a purposive population of this case study. Results show that based on the four stages of IMC framework, most respondents perceived selected Malaysia’s GLCs as practicing IMC concept in the respective organization. The highest mean score of M=3.909 was recorded on the perceived tactical coordination of marketing communication, followed by perceived commitment to market research in support of IMC (M=3.804), application of information technology in support of IMC (M=3.771), while the perceived strategic integration of IMC scored the lowest with mean score of M=3.756. Researcher also discovered that there is a weak relationship between the four stages of IMC framework and cultural dimension (r = 0.29, p < .01). This reflects that higher perceived cultural dimensions will result in higher IMC practice with regards to the four stages of IMC framework among GLCs top management. The findings in this study will be a great assistance for the management of GLCs to better utilize the tools in their marketing communications programmes. Empirical results of the present study will also allow researchers and senior management of GLCs to understand the function of IMC and use them more effectively